Microstructure and mechanical performance examination of 3D printed acrylonitrile butadiene styrene thermoplastic parts. Issue 11 (21st August 2020) - Gupta, Chhavi; MB, Pallavi; Shet, Nitesh Kumar; Ghosh, Anup K; Bandyopadhyay, Sumanda; Mukhopadhyay, Prasanta
Abstract: Fused filament fabrication (FFF) is a process where thermoplastic materials are heated to its melting point and then extruded, layer by layer, to create a three dimensional printed part. Printing occurs in a layered manner, which leads to creation of voids (air gaps) in the 3D printed parts. These voids act as centers for crack initiation, propagation and therefore resulting bulk mechanical properties are lower. This paper focuses on microstructural characterization and analysis of fused filament fabricated tensile test coupons made from acrylonitrile butadiene styrene polymer, at various design conditions. Comparable tensile modulus with injection molded specimens was obtained for FFF design condition that is, slice height (0.1778 mm), raster width (0.4064 mm), raster to raster air gap (−0.0015 mm), contour to raster air gap (−0.0508 mm) and raster angle (0°). Scanning electron microscope studies provided an understanding as to why FFF processed specimens yielded lower failure strain and an insight into the presence of intralayer voids in specimens having lower tensile modulus. The study confirmed that though bulk mechanicals were affected by the combined effect of inter, intra and interfacial voids, intravoids had a predominant influence. Abstract :